Implementation of Lean Management to Reduce Waste in Hemodialization Installation of QIM Batang Hospital - Kusdarmadji Kusdarmadji; Firman Pribadi; Iman Permana (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
Hospitals are efficient if they can use all available resources to produce something without leaving unwanted things. The purpose of the study was to determine the application of lean management in reducing waste in the Hemodialysis Installation of Qolbu Insan Mulia Hospital (QIM) Batang. This study uses a qualitative method with an Action Research research design whose results are presented narratively. The findings of this study indicate that there are three highest wastes, namely: waiting for waste (26%), motion waste (18%), and Defect waste (16%). There is a problem with waste waiting caused by a lack of human resources, in this case, the number of nurses, motion waste is caused by the movement of nurses who are too frequent in order to carry out inspections of patients undergoing HD and the large number of movements caused by inspections still using the manual method, and a waste defect found that HD failure was caused by anemia. Furthermore, there are efforts to reduce waste waiting, waste motion, and waste defect in the Hemodialysis Installation of Qim Hospital, Qolbu Insan Mulia Hospital (QIM).